Modification and analysis of layered materials with charged particle beams - Fox, Daniel (Trinity College (Dublin, Ireland). School of Physics, 2014)
In this work a range of highly focused charged particle beams were used to modify the structure and geometry of materials. Recently discovered two-dimensional (2D) materials were the focus of the work. Fundamental studies on the beam-sample interactions were conducted. This knowledge was then used to achieve nanoscale control of the modification.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin